Electromagnetic Structure of a Bound Nucleon - Gerstenberger, Rolf Volker (My University, 1973)
Effects of binding on the electromagnetic structure of a nucleon in a nucleus is examined for the two-pion part of the nucleon form factor. The nucleon is assumed to be bound in a harmonic oscillator potential and also coupled to the pion field through the Chew-Low type interaction. In the tight-binding limit, the nucleon structure approaches that given in the static Chew-Low theory, as expected, while the loose-binding limit gives the free nucleon case with nucleon recoil corrections. Implications of this binding on the magnetic moments of the tri-nucleon systems are investigated, and it is found that for a realistic strength of the harmonic oscillator potential the binding effect is too small to be very significant. Effects of the Pauli Principle are also discussed.
Keywords: physics; electromagnetic structure; bound nucleon; Pauli Principle